Protective effect of the Impella on the left ventricular function after acute broad anterior wall ST elevation myocardial infarctions with cardiogenic shock: cardiovascular magnetic resonance imaging strain analysis - Daisuke Fukamachi; Akimasa Yamada; Akihito Ohgaku; Yutaka Koyama; Hidesato Fujito; Riku Arai; Yasunari Ebuchi; Suguru Migita; Tomoyuki Morikawa; Masaki Monden; Norio Takei; Takehiro Tamaki; et al. (BMC Cardiovascular Disorders, 2022)
Abstract Background The clinical efficacy of the Impella for high-risk percutaneous coronary intervention (PCI) and cardiogenic shock remains under debate. We thus sought to investigate the protective effects on the heart with the Impella’s early use pre-PCI using cardiac magnetic resonance imaging (CMRI). Methods We retrospectively evaluated the difference in the subacute phase CMR imaging results (19 ± 9 days after admission) between patients undergoing an Impella (n = 7) or not (non-Impella group: n = 18 [12 intra-aortic balloon pumps (1 plus veno-arterial extracorporeal membrane oxygenation) and 6 no mechanical circulation systems]) in broad anterior ST-elevation myocardial infarction (STEMI) cases. A mechanical circulation system was implanted pre-PCI. Results No differences were found in the door-to-balloon time, peak creatine kinase, and hospital admission days between the Impella and non-Impella groups; however, the CMRI-derived left ventricular ejection fraction was significantly greater (45 ± 13% vs. 34 ± 7.6%, P = 0.034) and end-diastolic and systolic volumes smaller in the Impella group (149 ± 29 vs. 187 ± 41 mL, P = 0.006: 80 ± 29 vs. 121 ± 40 mL, P = 0.012). Although the global longitudinal peak strain did not differ, the global radial (GRS) and circumferential peak strain (GCS) were significantly higher in the IMPELLA than non-IMPELLA group. Greater systolic and diastolic strain rates (SRs) in the Impella than non-Impella group were observed in non-infarcted rather than infarcted areas. Conclusions Early implantation of an Impella before PCIs for STEMIs sub-acutely prevented cardiac dysfunction through preserving the GRS, GCS, and systolic and diastolic SRs in the remote myocardium. This study provided mechanistic insight into understanding the usefulness of the Impella to prevent future heart failure.